Pengaruh Atmosfer, Kualitas Produk dan Kualitas Layanan Terhadap Kepuasan Pelanggan Minuman Kopi pada Kedai “Kopi Dari Hati” di Kabupaten Bogor - Lorenza, Uyung; Susilowati, Isnurrini Hidayat; Marginingsih, Ratnawaty; Widiyanti, Wiwik (Lembaga Penelitian Universitas YARSI, 2025)
The development of business types in Indonesia is increasing, marked by the emergence of many new types of businesses, one of which is the culinary business. This situation has led to intense competition among business actors. The purpose of this study is to see the influence of atmosphere, product quality, and service quality on customer satisfaction with coffee drinks at the